Fear extinction learning improvement in PTSD after EMDR therapy: an fMRI study. Issue 1 (1st January 2019) - Rousseau, Pierre-François; El Khoury-Malhame, Myriam; Reynaud, Emmanuelle; Boukezzi, Sarah; Cancel, Aïda; Zendjidjian, Xavier; Guyon, Valérie; Samuelian, Jean-Claude; Guedj, Eric; Chaminade, Thierry; Khalfa, Stephanie
ABSTRACT: Objective : Neurobiological models of Posttraumatic Stress Disorder (PTSD) implicate fear processing impairments in the maintenance of the disorder. Eye Movement Desensitization and Reprocessing (EMDR) is one of the most efficient psychotherapies to treat PTSD. We aimed at exploring the brain mechanisms of the fear circuitry involved in PTSD patients' symptom remission after EMDR therapy. Method : Thirty-six PTSD participants were randomly assigned to either EMDR group receiving EMDR therapy or Wait-List (WL) group receiving supportive therapy. Participants underwent a behavioural fear conditioning and extinction paradigm during functional magnetic resonance (fMRI). In the EMDR group, patients were scanned at baseline, before EMDR and one week after remission. In the WL group, patients were scanned at baseline and within the same time interval as the EMDR group. Results : In the EMDR group after treatment, fear responses in the late extinction were significantly lower than before therapy. In parallel, significant functional activity and connectivity changes were found in the EMDR group versus the WL during the late extinction. These changes involve the fear circuit (amygdalae, left hippocampus), the right inferior frontal gyrus, the right frontal eye field and insula ( p FWE < .05). Conclusion : These functional modifications underlie a significant improvement of fear extinction learning in PTSD patients after EMDR therapy.